The living and the dead. [videorecording (DVD)] - Morgan, Colin, 1986-; Spencer, Charlotte (BBC, 2016)
A young couple inherits a farm and they are determined to start a beautiful new life together. However the home they have inherited starts to unleash unsettling and dangerous supernatural phenomena that starts to threaten their marriage.